Penetapan Batas Wilayah RT & RW Di Kelurahan Sembulang melalui Pemetaan Partisipatif - Gustin, Oktavianto; Roziqin, Arif; Rassarandi, Farouki Dinda; Triwinarko, Andy; Irawan, Sudra; Sari, Luthfiya Ratna; Chayati, Siti Noor; Pratama, Rizki Widi; Ghazali, Muhammad; Haiqal, Muhammad; Wandanita, Melia (Politeknik Negeri Batam, 2024)
The city of Batam as a tourist destination can be supported by regional development including the Sembulang sub-district area through the making of RT and RW area maps in Sembulang Sub-District/Village. This large-scale RT and RW map has a role as an official document that records administrative boundaries. Other spatial information in this map will later be needed in the development of the Kelurahan/Village to prepare spatial plans and inventory of village potential. In addition, these regional boundaries function to create administrative order, legal certainty so that it is expected to minimize boundary conflicts, regional fiscal calculations and identification of regional potential (Afdhalia et al., 2021; Lestari et al., 2020; Kemendagri. 2016; Budisusanto et al., 2014 ). The cartometric method can be used in determining and confirming Kelurahan/Village Boundaries in accordance with Geospatial Information Agency (BIG) regulations No.15 of 2019. So this year the community service team proposed kartometric Mapping of RT and RW Boundaries in Sembulang Village. In this service, a delineation of the RT and RW maps of Sembulang Village will be carried out. Determination of Boundaries through participatory mapping and FGD, and handing over the resulting products in the form of RT and RW Maps of Sembulang Village. The map of the boundaries of the RT RW Sembulang area was made with A3 paper size which was submitted to the Sembulang sub-district. This map contains information about the boundaries of the RT&RW areas in Sembulang Village as an information need for residents in Sembulang Village. Based on the results of these measurements, there were several changes to the rough map previously provided by the Sembulang Village, namely the expansion of one RT, which was originally 1 RT. From the results of this dedication, a map of the boundaries of the area was submitted to the Sembulang Village in print format.